2021
DOI: 10.1007/s00787-021-01748-z
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of treatments for attention deficit-hyperactivity disorder and autism spectrum disorder in children and adolescents: a systematic review

Abstract: Economic evaluations can help decision makers identify what services for children with neurodevelopmental disorders provide best value-for-money. The aim of this paper is to review the best available economic evidence to support decision making for attention deficit-hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) in children and adolescents. We conducted a systematic review of economic evaluations of ADHD and ASD interventions including studies published 2010–2020, identified through Econlit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 52 publications
(164 reference statements)
1
37
0
Order By: Relevance
“…The situation is not helped by the paucity of costeffectiveness evidence. A systematic review focused on children and adolescents 351 identified only two robust studies: one randomised controlled trial-based evaluation that suggested that the Preschool Autism Communication Trial intervention did not appear to be cost-effective in the short-term when added to treatment as usual, 273 and another that used modelling to estimate the potential costs and benefits of developmental early intervention programmes (ie, Early Start Denver Model) up to the age of 65 years, concluding that there would be cost savings and cost-effectiveness gains. 352 Another modelling study concluded that, even under optimistic assumptions, applied behaviour analysis was not cost-effective.…”
Section: Financial and Personal Costsmentioning
confidence: 99%
“…The situation is not helped by the paucity of costeffectiveness evidence. A systematic review focused on children and adolescents 351 identified only two robust studies: one randomised controlled trial-based evaluation that suggested that the Preschool Autism Communication Trial intervention did not appear to be cost-effective in the short-term when added to treatment as usual, 273 and another that used modelling to estimate the potential costs and benefits of developmental early intervention programmes (ie, Early Start Denver Model) up to the age of 65 years, concluding that there would be cost savings and cost-effectiveness gains. 352 Another modelling study concluded that, even under optimistic assumptions, applied behaviour analysis was not cost-effective.…”
Section: Financial and Personal Costsmentioning
confidence: 99%
“…Therefore, future research needs to identify molecular signal cascades and their connection to epigenetic modifications in the healthy and diseased brain. This also includes analyses of spatiotemporal dynamics of epigenetic mechanisms and patterns, hopefully elucidating cause, prevention or treatment of NDDs to increase quality of life for affected individuals and families ( Lamsal and Zwicker, 2017 ; Sampaio et al, 2021 ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…While there are now studies on adult treatments, a recent systematic review (Sampaio et al 2021) did not include these, and, importantly, included literature from a very limited time period (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020). Although data on adult treatments were included in the systematic review of Klora et al (2016), this review again only focused on pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%